Prevalences of and correlations between childhood trauma and depressive symptoms, anxiety symptoms, and suicidal behavior among institutionalized adolescents in Vietnam. (May 2021) - Pham, Tien Sy; Qi, Haiying; Chen, Dingxuan; Chen, Huilin; Fan, Fang
Abstract: Objectives: We investigated the prevalence rates of childhood trauma, depressive symptoms, anxiety symptoms and suicidal behaviors among Vietnamese adolescents and compared the differences between institutionalized adolescents (IAs) and noninstitutionalized adolescents (NIAs). In addition, we examined the multidimensional associations between childhood trauma and psychopathology among IAs. Methods: Five hundred forty-six participants were recruited into two groups (IAs and NIAs) matched by age, sex and grade. They completed a childhood trauma questionnaire, depression scale, anxiety scale, and 3 suicide-related questions. The chi-squared test and logistic regressions were performed. Results: The prevalences of anxiety symptoms and suicide attempts among IAs was higher than that among NIAs (25.6 % vs 14.7 %, p = 0.001 and 8.1 vs 3.7, p = 0.03, respectively), while the prevalences of other psychopathologies did not differ significantly. In the IA group, high prevalences of victimization through physical abuse (22.3 %), emotional neglect (57.9 %), and physical neglect (72.9 %) were found, and 58.6 % of the participants had experienced more than one type of trauma. These figures were significantly higher in IAs than in NIAs. Depression and suicidal ideation were more strongly correlated with emotional abuse and neglect than other types of maltreatment, while anxiety, suicide planning and suicide attempts were more strongly correlated with physical abuse. IAs who experienced more than two categories of trauma or greater intensity of trauma were more susceptible to developing depression, anxiety, and suicidal behaviors. Conclusions: Childhood trauma was multidimensionally associated with adverse psychological outcomes. We suggest that various aspects of childhood trauma, as well as psychopathologies, must be routinely assessed.